FENOMENA KOMUNIKASI MANUSIA SILVER DI KOTA PEKANBARU - Resti, Ririn Diani; Firdaus, Muhammad (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2023)
The existence of a silver man has become a phenomenon, in almost every red light in Pekanbaru City there is a silver man in action. Working to become a silver human for some people is a form of maintaining life in poverty. Even though you have to take a dangerous risk because painting your whole body with paint has dangerous risks. That's because the paint commonly used on silver humans is a textile dye. Which can cause itching and irritation and even cancer of the skin. This study aims to find out how the motives, meaning of work as a silver human being, and the communication experience of someone who works as a silver human being in Pekanabru City. This study uses a qualitative research method with a phenomenological approach. The research informants consisted of 5 people who were silver people in Pekanbaru City who were selected using a random sampling technique. Data collection techniques were carried out by means of in-depth interviews, observation, and documentation. This study uses interactive data analysis techniques which include three stages, namely data collection, data presentation and drawing conclusions. From the results of the study it can be seen that Silver's human motives consist of because motives which include demands to meet needs and entertain. And in order to motive is for the economy and solicitation of friends. Next is the meaning of silver human work is a source of income (main job) and as a part time job. And the silver human communication experience is divided into the first 2 tangs of pleasant (positive) communication experiences including getting good friends, getting family support and getting a good response. Unpleasant (negative) experiences include being chased out and looked down upon, often almost having accidents and being caught in raids. Keywords: Enomenology, Symbolic Interaction, Silver Man